Demonstration of Direction Dependent Conduction through MoS2 Films Prepared by Tunable Mass Transport Fabrication. (1st January 2016) - Chiappe, Daniele; Mongillo, Massimo; Asselberghs, Inge; Kazzi, Salim El; Caymax, Matty; Barla, Kathy; De Gendt, Stefan; Radu, Iuliana; Huyghebaert, Cedric
Abstract : This work focuses on the synthesis of MoS2 films grown by sulfurization of pre-deposited ultra-thin Mo films in the presence of a sulfur-containing gaseous precursor. The growth of high-quality TMDs requires careful control of specific thermodynamic and kinetic parameters. A deep understanding of mass transport mechanisms is achieved through a systematic investigation of the structural properties of MoS2 films grown using different sulfurization conditions. Mass transport smoothing is used to reduce surface roughness and fabricate MoS2 films in conformal contact with the underlying substrate. Oriented MoS2 films are obtained by combining kinetically controlled sulfurization conditions and the use of single crystal templates. Good uniformity and excellent conformity of layers over large area has enabled the synthesis of patterned MoS2 films which show anisotropic conduction properties.